PRELIMINARY DESIGN SISTEM PENYEDIAAN AIR BERSIH PADA KAMPUNG TEMATIK IKAN HIAS DI KAMPUNG SARASAH KECAMATAN BUNGUS TELUK KABUNG KOTA PADANG - Ridwan Ridwan; Vera Surtia Bachtiar; Reri Afrianita; Yega Serlina (BULETIN ILMIAH NAGARI MEMBANGUN, 2023)
Kampung Sarasah, as a thematic village, has had economic potential in the form of freshwater ornamental fish farming activities since 2020. The unavailability of a clean water supply system is one of the hindering factors for the growth and development of the area. Therefore, a preliminary study is needed for the provision of clean water supply in the area in the form of a preliminary design. This activity aims to provide a description and socialization of the technical plan for clean water supply in Kampung Sarasah, Padang City. The Preliminary design of the clean water supply system is carried out in Kampung Sarasah, Bungus Timur Village, Bungus Teluk Kabung Sub-District, Padang City. The preliminary design of the clean water supply system in Kampung Sarasah is conducted in several key stages, including a survey of the community's conditions and mapping of the Kampung Sarasah area, observation, socialization, and field measurements using Global Positioning System (GPS) equipment and the utilization of Google Earth application for selecting the route of transmission and distribution pipes for the clean water supply system plan. The capacity of the clean water treatment installation in the Kampung Sarasah area is 1.0 L/second, consisting of coagulation-flocculation unit, sedimentation unit, filtration unit, and disinfection unit. The capacity of the main distribution pipe network in the area is 1.2 L/second, using 2-inch HDPE pipes with a length of approximately 1.7 km. The estimated cost of the Sarasah Thematic Village Clean Water Supply System, based on community empowerment and excluding the procurement and construction of Water Treatment Plant and 15 m³ Reservoir, is Rp. 144,050,400. Following the preliminary design of the Sarasah Thematic Village Clean Water Supply System, it is recommended to proceed with detailed engineering design to support the smooth development of the system.